Bone-marrow-aspirate-concentrate for chondral defects: surgical techniques, clinical applications and basic science - Neubauer, Markus; Jeyakumar, Vivek; Muellner, Thomas; Nehrer, Stefan (Annals of Joint, 2018)
Mesenchymal stem or progenitor cells remain the cells of choice for many regenerative treatment strategies in orthopedics. Due to a number of reasons such as regulatory burdens, time- and cost-efficiency and patient safety, bone-marrow-aspirate-concentrate (BMAC) has become an increasingly important source for application of mesenchymal stem cells (MSCs). However, specific surgical application techniques, as well as treatment regimes, often remain poorly discussed in the literature. This article aims to bridge this gap by providing comprehensive information for practicing surgeons to ease patient selection and clinical application of BMAC for chondral defects.